2023
DOI: 10.3390/microorganisms11081920
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Properties of Pediococcus pentosaceus JBCC 106 and Its Lactic Acid Fermentation on Broccoli Juice

Abstract: To understand the biological roles of Pediococcus pentosaceus strains as probiotics isolated from the traditional Korean fermented food, Jangajji, Pediococcus pentosaceus was selected based on its high cinnamoyl esterase (CE) and antioxidant activities. The acid and bile stability, intestinal adhesion, antagonistic activity against human pathogens, cholesterol-lowering effects, and immune system stimulation without inflammatory effects were evaluated. Nitric oxide (NO) levels were measured in co-culture with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…P. pentosaceus has been highlighted for its probiotic effects, including its antibacterial mechanisms, such as the secretion of bacteriocins or bacteriocin-like substances (BLISs) to damage cell walls or to directly kill pathogenic bacteria, effectively combating bacterial threats [ 171 , 172 ]. A study conducted by Sang-Kyu et al showed that P. pentosaceus possesses potential activity against several bacterial species such as S. aureus , S. epidermidis , P. aeruginosa , P. Acnes , P. putida , S. xylosus , E. coli , B. cereus and B. vallismortis [ 173 ]. The use of specific strains of beneficial bacteria, such as Lactobacillus , Bifidobacterium , and B. coagulans , has been shown to target specific pathogens and modulate the immune system, enhancing the body’s natural defenses against infections.…”
Section: Role Of the Ngps In The Treatment And Control Of Human Diseasesmentioning
confidence: 99%
“…P. pentosaceus has been highlighted for its probiotic effects, including its antibacterial mechanisms, such as the secretion of bacteriocins or bacteriocin-like substances (BLISs) to damage cell walls or to directly kill pathogenic bacteria, effectively combating bacterial threats [ 171 , 172 ]. A study conducted by Sang-Kyu et al showed that P. pentosaceus possesses potential activity against several bacterial species such as S. aureus , S. epidermidis , P. aeruginosa , P. Acnes , P. putida , S. xylosus , E. coli , B. cereus and B. vallismortis [ 173 ]. The use of specific strains of beneficial bacteria, such as Lactobacillus , Bifidobacterium , and B. coagulans , has been shown to target specific pathogens and modulate the immune system, enhancing the body’s natural defenses against infections.…”
Section: Role Of the Ngps In The Treatment And Control Of Human Diseasesmentioning
confidence: 99%